DAKWAH ISLAMIYAH DAN TANTANGAN KONTEMPORER - W Warsito (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
Da’wah Islamiyah is a religious foundation that contains amar ma’ ruf nahi mungkar. Amar ma’ruf can contain direct invitation from people to do good thing or teach knowlegde. In the contemporary world, the teaching of knowlegde conducted by establishing Islamic education that has a vision to create a generation that figh ts for the religion of God on earth. While the nahi mungkar which prevents blame activities must be done in proportion to the blame activities themselves. One of blame activities in the contemporary world is the movement to convert Muslims and the destruction of Islamic teaching which caused by making methods of understanding religion that deviate from Islamic values.